The culture of environmental safety and the state of its formation - Donaeva Shaxnoza Abduraimovna (International Journal on Orange Technologies, 2020)
The article describes the formation of a culture of environmental safety in primary school students, its content, state of formation, form and methods, finding solutions to environmental security problems, environmental destruction or environmental situation, as well as the infrastructure for its teaching.